SUSi: CHATBOT PROMOTING PRIMARY HEALTHCARE KNOWLEDGE - dos Santos Albuquerque, Maíra; Souza Silva, Clóvis Daniel; Moreira Gomes, Dennis; Mesquita Mororó Pinto, Mayara; Passos de Vasconcelos, Suzane (Cadernos ESP, 2023)
Build a chatbot for the promotion of Primary Health Care for Community Health Agents (ACS) of the Family Health Strategy (ESF) in a municipality in Ceará. Methodological study of the technological production of a chatbot. For the construction of the technology, the Planning stages were followed, with an exploratory research being carried out with 143 ACS workers of the ESF in the municipality. Afterwards, the objectives, risk assessment and technology development were defined using the Dialogflow tool with integration to the Telegram communication channel. There were 79 responses to support the content to be promoted by the chatbot. The contents provided by the chatbot were organized into subthemes, the main theme being Primary Health Care in the context of the municipality of Acaraú. The use of chatbots provide new perspectives in the form of health promotion in the use of technological and innovative resources.
Keywords: Primary Health Care; Natural Language Processing; Information Technology